Analisa dan Perancangan Sistem Informasi Pencatatan Kegiatan Pembangunan Sarana & Prasarana Pada Program Kotaku Berbasis Gis dengan Gmaps Di Bkm Kelurahan Sungai Langkai - Fendi Hidayat; Muhamad Sigid Safarudin (LPPM Universitas Putera Batam, 2018)
KOTAKU is a nationally implemented program to build an integrated system for slums, where local governments lead and collaborate with stakeholders in planning and implementation, and promote community participation. So far, the report on the development of facilities and infrastructure has been done conventionally. This is very difficult for the community to see the development and benefits of the development program. to support the transparency process and to assist Kelurahan in monitoring the development progress of KOTAKU program, it is necessary to build a computerized information system to carry out the process of recording of Infrastructure Development Activities On or inventory of KOTAKU Program. In developing the system will use the waterfall development method. It is expected that with this information system can help BKM River Langkai in recording every development of facilities and infrastructure and can be used by the community to see and monitor the development of the process of development of facilities and infrastructure implemented at the KOTAKU program in BKM Sungai Langkai. So it can help the implementation of transparency in the implementation process of development activities.